Establishing a Framework for Gathering Structural and Social Determinants of Health in Alzheimer's Disease Research Centers. (17th December 2021) - Stites, Shana D; Midgett, Sharnita; Mechanic-Hamilton, Dawn; Zuelsdorff, Megan; Glover, Crystal M; Marquez, David X; Balls-Berry, Joyce E; Streitz, Marissa L; Babulal, Ganesh; Trani, Jean-Francois; Henderson, J Neil; Barnes, Lisa L; et al.
Abstract: Structural and social determinants of health (SSDoH) are environmental conditions in which individuals are born, live, learn, work, play, worship, and age that affect health, functioning, and quality-of-life outcomes across the life course. Growing evidence suggests that SSDoH can help to explain heterogeneity in outcomes in Alzheimer's disease and Alzheimer's disease and related dementias (AD/ADRD) research and clinical practice. The National Institute on Aging has prioritized collecting SSDoH data to elucidate disease mechanisms and aid discovery of disease-modifying treatments. However, a major nexus of AD/ADRD research, the national network of Alzheimer's Disease Research Centers (ADRCs), collects few SSDoH data. We describe a framework for feasibly gathering and modeling SSDoH data across ADRCs. We lay out key constructs, their measures, and empirical evidence for their importance in elucidating disease and prevention mechanisms. Toward a goal of translation, the framework proposes a modular structure with a core set of measures and options for adjunctive modules. We describe considerations for measuring SSDoH in existing geographically and culturally diverse research cohorts. We also outline a rationale for universal implementation of a set of SSDoH measures and juxtapose the approach with alternatives aimed at collecting SSDoH data.